Writing as Material Practice Substance, surface and medium - Piquette, Kathryn; Open Textbook Library (Open Textbook Library, 2013)
Writing as Material Practice grapples with the issue of writing as a form of material culture in its ancient and more recent manifestations, and in the contexts of production and consumption. Fifteen case studies explore the artefactual nature of writing - the ways in which materials, techniques, colour, scale, orientation and visibility inform the creation of inscribed objects and spaces, as well as structure subsequent engagement, perception and meaning making. Covering a temporal span of some 5000 years, from c.3200 BCE to the present day, and ranging in spatial context from the Americas to the Near East, the chapters in this volume bring a variety of perspectives which contribute to both specific and broader questions of writing materialities. The authors also aim to place past graphical systems in their social contexts so they can be understood in relation to the people who created and attributed meaning to writing and associated symbolic modes through a diverse array of individual and wider social practices.
Chapter 1. Introduction: Developing an approach to writing as material practice (Kathryn E. Piquette and Ruth D. Whitehouse) -- Chapter 2. The Twisting Paths of Recall: Khipu (Andean cord notation) as artifact (Frank Salomon) -- Chapter 3. Writing as Material Technology: Orientation within landscapes of the Classic Maya world (Sarah E. Jackson) -- Chapter 4. Writing (and Reading) as Material Practice: The world of cuneiform culture as an arena for investigation (Roger Matthews) -- Chapter 5. Re-writing the Script: Decoding the textual experience in the Bronze Age Levant (c.2000-1150 bc) (Rachael Thyrza Sparks) -- Chapter 6. The Function and Meaning of Writing in the Prehistoric Aegean: Some reflections on the social and symbolic significance of writing from a material perspective (Helène Whittaker) -- Chapter 7. Form Follows Function: Writing and its supports in the Aegean Bronze Age (Sarah Finlayson) -- Chapter 8. Materiality of Minoan Writing: Modes of display and perception (Georgia Flouda) -- Chapter 9. Saving on Clay: The Linear B practice of cutting tablets (Helena Tomas) -- Chapter 10. Straight, Crooked and Joined-up Writing: An early Mediterranean view (Alan Johnston) -- Chapter 11. "It Is Written"?: Making, remaking and unmaking early 'writing' in the lower Nile Valley (Kathryn E. Piquette) -- Chapter 12. Written Greek but Drawn Egyptian: Script changes in a bilingual dream papyrus (Stephen Kidd) -- Chapter 13. The Other Writing: Iconic literacy and Situla Art in pre-Roman Veneto (Italy) (Elisa Perego) -- Chapter 14. 'Tombstones' in the North Italian Iron Age: Careless writers or athletic readers? (Ruth D. Whitehouse) -- Chapter 15. Different Times, Different Materials and Different Purposes: Writing on objects at the Grand Arcade site in Cambridge (Craig Cessford) -- Chapter 16. Writing Conservation: The impact of text on conservation decisions and practice (Elizabeth Pye) -- Chapter 17. Epilogue (John Bennet)
In English.
Description based on online resource
Keywords: Humanities -- Textbooks; Rhetoric -- Textbooks